2017
DOI: 10.1002/anie.201612494
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in Gold Finger Structure Elucidated by Traveling‐Wave Ion Mobility Mass Spectrometry

Abstract: Traveling wave ion mobility (TWIM) mass spectrometry (MS) is a powerful method for the structural and conformational analysis of proteins and peptides, enabling the differentiation of isomeric peptides (or proteins) that have the same sequence but are modified at different residues. In this study, the TWIM-MS technique was used to separate isomeric Au metallopeptide ions that were formed by Zn displacement from the parent zinc fingers (ZFs). The synthetic gold finger peptides were derived from the C-terminus o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 41 publications
2
24
0
Order By: Relevance
“…[1a, 3] We took this approacha nd isolated ac onstruct of TTP called TTP-2D, which contains the protein'st wo CCCH domains.W eh ave previously reported the cloning, overexpression and purification of TTP-2D, and demonstrated that it is highly soluble, binds and folds aroundz inc, and functions (selectively recognize AU-rich mRNA targets)( Figure 1A,B). [13b, 19] Au III terpy is soluble in aqueous solution and it exhibits rich spectroscopy (charge-transfer bands) that are sensitive to metal coordination, allowing for reactivity to be followed optically.M oreover,t here are severalr ecent reports of the interaction of gold complexes,i ncluding Au III terpy,w ith ZF peptides, including Cys 4 "zinc ribbon"s ites, [13b] Cys 2 HisCys "zinc knuckle", [12,14,20] Cys 2 HisCys( PARP-1), [13,21] andC ys 2 His 2 classical ZF, [12a,c, 14, 22] and consensus peptide1(Cys 2 His 2 ). [13b, 19] Au III terpy is soluble in aqueous solution and it exhibits rich spectroscopy (charge-transfer bands) that are sensitive to metal coordination, allowing for reactivity to be followed optically.M oreover,t here are severalr ecent reports of the interaction of gold complexes,i ncluding Au III terpy,w ith ZF peptides, including Cys 4 "zinc ribbon"s ites, [13b] Cys 2 HisCys "zinc knuckle", [12,14,20] Cys 2 HisCys( PARP-1), [13,21] andC ys 2 His 2 classical ZF, [12a,c, 14, 22] and consensus peptide1(Cys 2 His 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[1a, 3] We took this approacha nd isolated ac onstruct of TTP called TTP-2D, which contains the protein'st wo CCCH domains.W eh ave previously reported the cloning, overexpression and purification of TTP-2D, and demonstrated that it is highly soluble, binds and folds aroundz inc, and functions (selectively recognize AU-rich mRNA targets)( Figure 1A,B). [13b, 19] Au III terpy is soluble in aqueous solution and it exhibits rich spectroscopy (charge-transfer bands) that are sensitive to metal coordination, allowing for reactivity to be followed optically.M oreover,t here are severalr ecent reports of the interaction of gold complexes,i ncluding Au III terpy,w ith ZF peptides, including Cys 4 "zinc ribbon"s ites, [13b] Cys 2 HisCys "zinc knuckle", [12,14,20] Cys 2 HisCys( PARP-1), [13,21] andC ys 2 His 2 classical ZF, [12a,c, 14, 22] and consensus peptide1(Cys 2 His 2 ). [13b, 19] Au III terpy is soluble in aqueous solution and it exhibits rich spectroscopy (charge-transfer bands) that are sensitive to metal coordination, allowing for reactivity to be followed optically.M oreover,t here are severalr ecent reports of the interaction of gold complexes,i ncluding Au III terpy,w ith ZF peptides, including Cys 4 "zinc ribbon"s ites, [13b] Cys 2 HisCys "zinc knuckle", [12,14,20] Cys 2 HisCys( PARP-1), [13,21] andC ys 2 His 2 classical ZF, [12a,c, 14, 22] and consensus peptide1(Cys 2 His 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…We first measured the native ESI-MS of apo-TTP-2D, shown in FigureS2A Figure 3A)w as then obtained, to confirmt hat we could obtain the native metal-bound species forT TP-2D. [14] In the analogous experiment with apo-TTP-2D plus Au III terpy,s imilarp roducts were observed, as showni nF igure S2 Ba nd Figure S4 (Supporting Information). The native ESI-MS of Zn II 2 -TTP-2D + 2equiv of Au III terpy was then recorded.…”
Section: Nativee Si-ms To Identify Reaction Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meier et al studied the interaction of a series of gold(III) compounds (both organometallic and coordination, 8-12) with biologically relevant nucleophiles by ESI-MS. [5] Compound 8 reacts readily with 9-ethylguanine (EtG). Organometallic compounds 9 and 10 show only very minor MS signals for EtG adducts even after 24 h. Readily detectable EtG adducts were observed for 11.…”
Section: Protein Targeting and Inhibitionmentioning
confidence: 99%
“…Curiously enough, the first uses of gold(I) compounds in treatment of rheumatoid arthritis were based on the idea that such illness was caused by a bacterial infection, which was shown to be incorrect. [1] Mirroring the historical application of gold and goldcontaining compounds for the treatment of such a wide variety of diseases, the 2016-2017 period has introduced gold-based metallodrugs for applications including the molecular understanding of the mechanisms of interaction with protein targets [3][4][5][6][7][8] and development of new therapeutic agents for HIV, cancer, [9,10] bacterial infections [11] as well as parasitic infections. [12] Platinum compounds, on the other hand, were intensively studied since the middle 1960's after the serendipitous discovery of the antitumor activity of cisplatin by Rosenberg.…”
Section: Introductionmentioning
confidence: 99%